Loss, Bereavement and Creativity: Meanings and Uses. (October 2015) - Brennan, Michael
Within the field of death and bereavement studies, the assumption that loss and bereavement provide the spur to creativity has become so widespread as to assume the status of a conventional wisdom. With this in mind, this article surveys the literature on the topic, extant, and contemporary, revealing its diffuseness as well as the multidisciplinary synergies produced by those working in disparate academic and clinical fields of practice. In so doing, the article explores what it means to be creative in the context of loss and bereavement, the potential for self-development and personal growth offered by creativity and loss, the theoretical premises linking creativity and loss, and the application and challenges for creative therapies in the institutional context of hospice and palliative care.